Word – paradigmatical image – icon. About intersemiotics in Orthodox Slavonic culture of the Middle Ages - Dziadul, Paweł (Poznańskie Studia Slawistyczne, 2012)
This  work  deals  with  the  problem  of  intersemiotics  in  Orthodox  Slavonic  culture  in  the Middle Ages. Attention here is focused on the source, essence and ontology of correspondence of the arts. Despite the fact that in the Middle Ages word and image (icons, frescos, miniatures of manuscripts) had completely different specificity of signs, they were connected with each other on a different level of perception. According to the Church Fathers (John of Damascus, Maximus the Confessor, Basil the Great) and East Christian mysticism (Pseudo Dionysius the Areopagite), the art of the written word and visual art had the same aim and function,  because  they  referred  to  eternal  and  spiritual reality  and  to  the  divine  archetype. The ontology of the word and icon was linked to the specific version of Pseudo-Dionysius’ symbolism. Moreover, this symbolism is connected with the term – “paradigmatical image”, functioning beyond text and iconography, in the iconosphere of the Orthodox Middle Ages. Paradigmatical image becomes a specific link between a word and an icon. Of course, paradigmatical images  were  created  on  the  basis  of  Biblical  (and/or  apocryphal)  and  Patristic Byzantine texts, although they started to function  regardless of their original context. This work presents the way paradigmatical images function in Orthodox iconography and literature (the Raising of Lazarus, the Last Judgement, the Trinity).